2022
DOI: 10.3390/ijerph19031055
|View full text |Cite
|
Sign up to set email alerts
|

Do Employee Stock Ownership Plans Affect Corporate Social Responsibility? Evidence from China

Abstract: Few studies have discussed the relationship between employee stock ownership plans (ESOPs) and corporate social responsibility (CSR). Using a sample of 895 A-share public firms in China, this research examines the effects of ESOPs on CSR, and the moderating effects of wedge structure and firm size on this relationship. This research mainly used the OLS model to test the research hypotheses, and all regressions were performed in Stata15. The results show that the ESOPs of Chinese public firms provide external e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…During this period, with the approval of the China Securities Regulatory Commission, state-owned enterprises could issue some equity to internal employees to improve operational efficiency. However, due to imperfect implementation details and a lack of effective supervision, the ESOPs not only failed to improve corporate performance [ 26 ], but also caused serious problems such as the transmission of benefits and the loss of state-owned assets [ 22 ]. For these reasons, the China Securities Regulatory Commission terminated the internal employee stock ownership of listed enterprises in December 1998.…”
Section: Institutional Background Literature Review and Hypothesis De...mentioning
confidence: 99%
See 4 more Smart Citations
“…During this period, with the approval of the China Securities Regulatory Commission, state-owned enterprises could issue some equity to internal employees to improve operational efficiency. However, due to imperfect implementation details and a lack of effective supervision, the ESOPs not only failed to improve corporate performance [ 26 ], but also caused serious problems such as the transmission of benefits and the loss of state-owned assets [ 22 ]. For these reasons, the China Securities Regulatory Commission terminated the internal employee stock ownership of listed enterprises in December 1998.…”
Section: Institutional Background Literature Review and Hypothesis De...mentioning
confidence: 99%
“…Chang et al (2015) [ 18 ] provided empirical evidence that non-executive employee stock options have a positive impact on corporate innovation. Zhou et al (2022) [ 22 ] found that ESOPs improve corporate CSR performance by providing employees with external economic incentives and internal psychological incentives.…”
Section: Institutional Background Literature Review and Hypothesis De...mentioning
confidence: 99%
See 3 more Smart Citations